2017
DOI: 10.1002/mrm.26812
|View full text |Cite
|
Sign up to set email alerts
|

Effect of myelin water exchange on DTI‐derived parameters in diffusion MRI: Elucidation of TE dependence

Abstract: The exchange between myelin and intra/extra-axonal water pools often plays a non-negligible role in the observed TE dependence of diffusion parameters, which may accompany or alter the effect of intrinsic T in causing such dependence. The TE dependence may potentially serve as a biomarker for demyelination processes (e.g., in multiple sclerosis and Alzheimer's disease). Magn Reson Med 79:1650-1660, 2018. © 2017 International Society for Magnetic Resonance in Medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…The FA maps from DDE do not show differences in NAWM, which suggests that differences in diffusion times, echo time, or b‐value (Table ) may be contributing to the differential detection of FA and μFA in the global NAWM rather than image resolution. This is supported by previous work, which has shown that in vivo FA measurements of the brain are sensitive to echo time and may be biased at high b‐value in a tissue‐dependent manner. However, previous studies suggest that FA values are largely insensitive to changes in diffusion time .…”
Section: Discussionsupporting
confidence: 83%
“…The FA maps from DDE do not show differences in NAWM, which suggests that differences in diffusion times, echo time, or b‐value (Table ) may be contributing to the differential detection of FA and μFA in the global NAWM rather than image resolution. This is supported by previous work, which has shown that in vivo FA measurements of the brain are sensitive to echo time and may be biased at high b‐value in a tissue‐dependent manner. However, previous studies suggest that FA values are largely insensitive to changes in diffusion time .…”
Section: Discussionsupporting
confidence: 83%
“…An histology-based computational model was able to explain in vivo T 2 relaxometry from the rat spinal cord using different T 2 values for the intra- and extra-axonal environments, but not if they were constrained to be equal (Harkins et al, 2012). And some recent studies have reported echo time dependence of water diffusion characteristics in white matter (Lin et al, 2017; Qin et al, 2009; Veraart et al, 2017).…”
Section: T2mentioning
confidence: 99%
“…Though one may prefer to include a third compartment, which is strongly restricted in all directions to represent water trapped inside cell bodies or other small compartments, recent studies using high b ‐values and isotropic diffusion weighting suggested that the contribution from stationary water would be below the detection limit. Also, though the water within myelin is often neglected in diffusion models because of its short T 2 relaxation time, recent studies have suggested a subtle but significant contribution from the finite exchange with the myelin water pool. The exchange between the two compartments is negligible. The intra‐neurite pre‐exchange lifetime in normal myelinated white matter is reportedly about a second, and is regarded as sufficiently long compared with the diffusion time. The diffusion time ( t ) is sufficiently long that diffusion within each compartment can be approximated as Gaussian .…”
Section: Theorymentioning
confidence: 99%
“…Though one may prefer to include a third compartment, which is strongly restricted in all directions to represent water trapped inside cell bodies or other small compartments, 22 recent studies using high b-values 45 and isotropic diffusion weighting 46 suggested that the contribution from stationary water would be below the detection limit. Also, though the water within myelin is often neglected in diffusion models because of its short T 2 relaxation time, recent studies 47,48 have suggested a subtle but significant contribution from the finite exchange with the myelin water pool.…”
Section: Model Assumptionsmentioning
confidence: 99%